Disinfection Procedures in Dental Office: An Overview - Nihar Ranjan Sahoo1, Rashmita Sahoo2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Disinfection & Sterilization if done properly, it can prevent transmission of many diseases among thedoctors, healthcare personnel and patients. The risk of infection is high in the dental office because the oralcavity is rich in aerobic, anaerobic bacterial flora and many viral pathogens. The method of disinfection andsterilization depends on the use of the medical devices: Critical instruments (pierce the tissue) should besterilized, Semi critical instruments (come in contact with the mucosa) should be sterilized & Least criticalinstruments (touch the Surfaces during treatment) & should be disinfected. Cleaning should be done byhigh-level disinfection and sterilization. Current guidelines of disinfection and sterilization must be strictlyfollowed by doctors, healthcare personnel.